Interpretasi Psikologis Lirik Lagu Album “Naura & Genk Juara” Karya Mhala dan Tantra Numata - Hayati, Risda; Sukenti, Desi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Songs can be a means of communication that singers and songwriters want to convey to listeners about what they feel. In songs, there are song lyrics which are part of literary works which contain outpourings of personal feelings, emotions, and expressions of soul experiences in the form of an arrangement of words. One of them is the song lyrics on the album Naura & Genk Juara. The lyrics on the album contain many implied meanings, so analysis is needed using Schleimacher's Hermeneutics theory which is used to understand the meaning of the song from the psychology of the song writer. The aim of the research is to describe, analyze and interpret the psychology of the song lyrics on the album Naura & Genk Juara. The method used in this research is descriptive qualitative. Data collection techniques include (1) listening to the song carefully, (2) noting the song lyrics carefully, (3) understanding the psychological aspects of the song. Data analysis uses Schleirmacher's hermeneutical approach. The results of the research show that Schleilmacher's psychological interpretation on the album song Naura & Genk Juara describes enthusiasm and never giving up on being a champion, parents' anxiety about their children, preserving nature, annoyance with friends, motivation for having dreams, regrets for children who don't listen to their parents' advice, optimism about being a winner, and friendship.  At the psychological interpretation stage, it can be seen that the lyrics he wrote were created from phenomena that were occurring at that time, many Indonesian children were not mentally strong enough to face challenges in achieving their dreams, so lyrics emerged that provided motivation, besides that, many Indonesian children who do not want to listen to advice from their parents, causing regret.